Elucidating the associations of polymorphism of growth hormone gene with milk production traits in Jamunapari goats of India - Mandal, Ajoy; Prajapati, B. K; Singh, K. P; Rout, P. K.; Roy, R. (Indian Journal of Dairy Science, 2024)
Growth hormone (GH) gene can be utilized as a major gene because its polymorphisms have been associated to milk traits in various livestock species. The aim of this present study was to investigate single-strand conformation polymorphism (SSCP) in the exon 1, 3 and 5 of gGH (goat GH) gene and to evaluate the possible associations with milk traits in Jamunapari goat, maintained at the ICAR- Central Institute for Research on Goats, Makhdoom, Uttar Pradesh, India. In this study, 100 primiparous lactating goats were randomly chosen, and their productive performances like 90-days, 140-days and total milk yield as well as milk compositional traits like fat %, SNF%, casein%, protein%, lactose% and ash % of three consecutive lactations were recorded. The exon 1, 3 and 5 of the gGH gene was PCR amplified and the resulting products were analyzed by SSCP. Two conformational patterns (A and B) for each the GH exon 3 and 5 were detected but no polymorphism existed in exon 1 of growth hormone gene.The frequency of the patterns varied from 41.4 to 58.6% in these two fragments. Association studies of SSCPs patterns at GH gene with milk production and milk composition traits in Jamunapari breed showed that only polymorphic patterns at exon 3 were positively associated with milk production traits, i.e., with 90-days milk yield, 140-days milk yield and total milk yield of animals but there was no significant effect on milk composition traits. Animals with pattern A/A for exon 3 were significantly superior milk producers (P